2020
DOI: 10.37358/rc.20.7.8252
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Hypoglycemic Agents in Surface Water Samples Using SPE-LC-MS/MS Method

Abstract: Antidiabetic compounds are a class of emerging contaminants in environment, for which there are no regulations in the world environmental legislation. These compounds are among the most widely used drugs in the world due to the large number of patients with diabetic conditions. The presence of these pollutants in the environment is insufficiently studied, so efficient analytical methods are needed to allow their detection at trace levels (ng/L). For the simultaneously quantification of the five antidiabetics (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
0
0
Order By: Relevance
“…Although all of these substances are extensively metabolised in the human body and only small portions of the drugs are excreted unchanged (Brocker et al, 2020;Latini et al, 1984;Talreja and Cassagnol, 2022), they have been repeatedly found in surface waters in concentrations ranging from ng/l to hundreds of ng/l (Batt et al, 2015;de Barros et al, 2018;Iancu et al, 2020;Komesli et al, 2015;Santos et al, 2013).…”
Section: Antiarrhythmic Drugsmentioning
confidence: 99%
“…Although all of these substances are extensively metabolised in the human body and only small portions of the drugs are excreted unchanged (Brocker et al, 2020;Latini et al, 1984;Talreja and Cassagnol, 2022), they have been repeatedly found in surface waters in concentrations ranging from ng/l to hundreds of ng/l (Batt et al, 2015;de Barros et al, 2018;Iancu et al, 2020;Komesli et al, 2015;Santos et al, 2013).…”
Section: Antiarrhythmic Drugsmentioning
confidence: 99%